2007
DOI: 10.1007/s10508-007-9262-4
|View full text |Cite
|
Sign up to set email alerts
|

Finger Length Ratio (2D:4D) in Adults with Gender Identity Disorder

Abstract: From early childhood, gender identity and the 2nd to 4th finger length ratio (2D:4D) are discriminative characteristics between sexes. Both the human brain and 2D:4D may be influenced by prenatal testosterone levels. This calls for an examination of 2D:4D in patients with gender identity disorder (GID) to study the possible influence of prenatal testosterone on gender identity. Until now, the only study carried out on this issue suggests lower prenatal testosterone levels in right-handed male-to-female GID pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 23 publications
3
22
0
6
Order By: Relevance
“…In accordance with the present results, Schneider, Pickel, and Stalla (2006) as well as Kraemer et al (2009) found evidence for more female-typical 2D:4D ratios in a group of 63 adult males diagnosed with GID, especially when restricting the analysis to right-handed subjects. This finding supports the hypothesis that men with GID might have been exposed to lower levels of androgen during early development.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the present results, Schneider, Pickel, and Stalla (2006) as well as Kraemer et al (2009) found evidence for more female-typical 2D:4D ratios in a group of 63 adult males diagnosed with GID, especially when restricting the analysis to right-handed subjects. This finding supports the hypothesis that men with GID might have been exposed to lower levels of androgen during early development.…”
Section: Discussionsupporting
confidence: 92%
“…The digit ratio also has been studied in transsexuals, yielding a higher digit ratio in MtF transsexuals than in control males, similar to control females. By contrast, the digit ratio of FtM transsexuals was found to be in the range of control females (Kraemer et al, 2009;Schneider, Pickel, & Stalla, 2006). The findings support the assumption of prenatal testosterone exposure as etiological factor of transsexualism, at least for MtF transsexualism.…”
Section: Page 8 Of 64supporting
confidence: 62%
“…Among studies using a 7-point Kinsey-like scale (which ranges from 0 to 6) to assess sexual orientation, homosexuals have been categorized as those with a score of 6 (e.g., Hall & Schaeff, 2008), with a score of 5 and 6 (e.g., Rahman, 2005), or with a score equal to or higher than 2 (e.g., Kangassalo et al, 2011;Rahman & Wilson, 2003a, b). Studies using the 9-point Kinsey-like scale (which ranges from 1 to 9) to assess sexual orientation have classified individuals with a total score of 11 or less on three items as homosexuals (Kraemer et al, 2006(Kraemer et al, , 2009. Additionally, some studies categorized individuals according to participants' own choice of descriptor: heterosexual, homosexual, or bisexual (e.g., Lippa, 2003;Manning et al, 2007).…”
Section: Introductionmentioning
confidence: 99%